Enchanted [videorecording (DVD)] - Kelly, Bill; Adams, Amy; Marsden, James, 1973-; Menzel, Idina; Sarandon, Susan, 1946-; Dempsey, Patrick, 1966-; Spall, Timothy, 1957-; Covey, Rachel; Andrews, Julie; Burgess, Don, 1956-; Baxter, James, 1967-; Menken, Alan; et al. (Disney DVD., 2008)
The beautiful princess Giselle is banished from the animated land of Andalasia by the evil queen. She finds herself in the gritty streets of the real, modern-day Manhattan. Shocked by this strange new environment that does not operate on a "happily ever after" basis, Giselle find herself adrift in a chaotic world that is badly in need of enchantment. Giselle begins to fall in love with the cynical, no-nonsense divorce lawyer who has come to her aid. Little does he realize that this joyful, wide-eyed innocent is about to enchant him